A Longitudinal Assessment Of Standing Balance In Healthy Adults. Issue 5 (20th October 2017) - Simmons, Roger W.; Levy, Susan S.; Simmons, Nicole K.
ABSTRACT: Background/Study Context : The study was a longitudinal assessment of age-related changes in standing balance and response strategy usage in healthy adults. Methods : Balance of 17 individuals with a mean age of 44.5 years was assessed and then reassessed 19.5 years later. Participants stood on computer-controlled dual-force platforms enclosed by a visual surround and completed six tests in which visual and/or somatosensory information was systematically degraded or eliminated. Results : Results for each test and a weighted composite balance score revealed no significant change in postural control over the time period studied. However, response strategy scores indicated some significant change with age. Specifically, compensatory movement corrections about the ankle complex increased when standing on a stable support surface with and without vision, and hip-centered corrections were prominent when standing on an unstable surface with eyes open or closed. Conclusion : Increased reliance on response strategy usage with time is interpreted as a compensatory adjustment to age-related increases in postural instability and accounts for the absence of any change in standing balance under different conditions of sensory input.